Genotype-Phenotype Interactions In Pediatric Obstructive Sleep Apnea - Kheirandish-Gozal, Leila (2013)
Pediatric sleep disordered breathing (PSDB) is not only a very frequent condition affecting 2–4% of all children, but is also associated with an increased risk for a variety of manifestations underlying end-organ injury and dysfunction that impose both immediate and potentially long-term morbidities and corresponding inherent elevations in healthcare costs. One of the major problems with the creation of valid algorithms aiming to stratify diagnostic and treatment prioritization lies in our current inability to predict and identify those children who are most at-risk for PSDB-induced adverse consequences. Thus, improved our understanding of the mechanisms governing phenotype variance in PSDB is essential. Here, we examine some of the potential underpinnings of phenotypic variability in PSDB, and further propose a conceptual framework aimed at facilitating the process of advancing knowledge in this frequent disorder.